Instrumen Penelitian Pada Pengukuran Kesiapan Tenaga Kesehatan di Era Covid-19 - Failenggo, Erie; Achadi, Anhari (An Idea Health Journal, 2022)
Most all the countries in the world haven’t been prepared for COVID - 19 pandemic so there is a need to analyze the strategies to measure our healthcare workers’ preparedness for preventing healthcare workers (HCW) from becoming the victim of covid-19. This systematic literature review is for reviewing the various assessment tools that had been used to measure the preparedness of healthcare workers’ for COVID - 19 in the time of pandemic of COVID-19 (2019 November - 2021 June). Between this range of time, we analyzed how the researchers defined and constructed the assessments tool for measuring the preparedness of healthcare workers for COVID-19. We used databases of Scopus, Proquest, Pubmed, and Willey online library with search themes healthcare workers, Preparedness, Covid-19, assessment. There were 33 studies that measured HCW’s preparedness for COVID-19 from November 2019 to 10 June 2021. Most studies were done in developing Nations (N=22). Almost of studies were Cross-sectional studies with questionnaires as their main instrument. The definition of preparedness was varied among these studies but all of them agreed that the tool for measuring the preparedness of HCW for COVID-19 was constructed with more than one aspect of measurement.